The Double Burden Of Aging And Disability: An Analysis Of Disability Prevalence Among Older Adults In Indonesia (Based On The 2023 Indonesian Health Survey) - Pariawan Lutfi Ghazali; Suryo Ediyono (Journal Hygeia Public Health, 2026)
Background: Indonesia is currently undergoing a demographic transition characterized by a growing proportion of older adults, while simultaneously facing an increasing burden of disability associated with the aging process. The 2023 Indonesian Health Survey (Survei Kesehatan Indonesia/SKI) provides the most recent nationally representative data on health conditions, including disability across different age groups. Objective: This study aims to analyze the prevalence of disability, levels of functional dependency, risk factors, and the availability of caregiving among the elderly population in Indonesia based on data from the 2023 Indonesian Health Survey. Methods: A cross-sectional study design was employed using secondary data from the 2023 Indonesian Health Survey. A total of 97,339 individuals aged ≥60 years were analyzed for dependency status using the Barthel Index of Activities of Daily Living (ADL), while 863,402 individuals aged ≥1 year were included in the analysis of sensory and motor disabilities. Descriptive analyses were conducted to examine prevalence distributions by province, sociodemographic characteristics, and comorbid conditions. Results: The national prevalence of disability (visual, hearing, or mobility impairment) was 1.2% among individuals aged ≥1 year, with an exponential increase among older age groups: 5.4% among those aged 65–74 years and 15.1% among those aged ≥75 years. Overall, 95.0% of adults aged ≥60 years remained functionally independent according to the Barthel Index ADL. However, dependency increased substantially among those aged 80 years and older, with 16.7% classified as dependent. Stroke was identified as the comorbidity associated with the highest risk of dependency, with 37.6% of older adults with stroke experiencing functional dependence. Family members served as the primary caregivers for 80.8% of dependent older adults, whereas only 1.3% received care from formally trained elderly care providers. Conclusion: Indonesia is facing a double burden of population aging and disability, requiring comprehensive policy responses. These include strengthening primary healthcare services for older adults, enhancing the capacity of family caregivers, and developing community-based early detection programs for disability.